Prevalence and calcification of stylohyoid complex in North West part of India and its correlation with general and dental health condition - Shalu Rai; Deepankar Misra; Nivedita Singh; Mansi Khatri; Kuber Tyagi; Priyank Mallick (Wolters Kluwer Medknow Publications, 2017)
Aim: This study was conducted to evaluate the variation and clinical significance of stylohyoid complex and to correlate it with general and dental health among different age groups and gender using panoramic radiographs. Materials and Methods: The study included 1,000 subjects indicated for panoramic radiographs. Styloid processes >30 mm were correlated age wise and gender wise. The morphology of the calcified stylohyoid complexes was allocated into 12 different patterns and their length was measured directly on the radiographs. Serum calcium levels and cholesterol levels were obtained from subjects with elongated styloid process and their heart rate, blood pressure measurement, weight, height, number of teeth present, and community periodontal index (CPI) was assessed. Results: Out of 978 detected styloid processes, 267 (27.3%) were more than 30 mm. The average length of the calcified styloid complex was 26.40 mm. The most common pattern of calcification was found to be E pattern, 64 (34.03%) in number which had statistically significant correlation with age (P value <0.001). Pearson's correlation coefficient association of body weight with elongated styloid process (left and right) was 0.163 (P value 0.162) and 0.300 (P value 0.001) respectively which was found to be statistically significant on right side. Twenty seven subjects who showed no elongation but evident calcification patterns according to gender and age on panoramic radiographs were also recorded and were called mineralized styloid termed as mineralization. Conclusion: Calcification of the styloid complex is commonly observed on panoramic radiographs and the present and previous studies indicate that the panoramic radiographs include information on general and dental health condition.